2018
DOI: 10.3928/01477447-20171127-02
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Persistent Pain After Fixation of Distal Clavicle Fractures in an Active Military Population

Abstract: Patients who undergo open reduction and internal fixation of distal clavicle fractures have a high rate of hardware removal and persistence of symptoms, particularly when attempting to return to high-demand activities. This study evaluated the outcomes of military servicemembers after surgical treatment of distal clavicle fractures. The authors performed a retrospective analysis of active duty servicemembers who underwent open reduction and internal fixation of Neer type II distal clavicle fractures between Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Less frequently used PROMs—and therefore not analyzed in this study—were the Subjective Shoulder Value, Oxford Shoulder Score, and QuickDASH (used 7, 6, and 4 times, respectively). Three studies 15,17,37 used an unusual questionnaire, and 3 studies 11,30,68 did not use any PROM. The data of 1 study 72 were not adaptable for analysis owing to division of its population into subgroups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Less frequently used PROMs—and therefore not analyzed in this study—were the Subjective Shoulder Value, Oxford Shoulder Score, and QuickDASH (used 7, 6, and 4 times, respectively). Three studies 15,17,37 used an unusual questionnaire, and 3 studies 11,30,68 did not use any PROM. The data of 1 study 72 were not adaptable for analysis owing to division of its population into subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…Fair Quality Poor Quality Baunach et al 3 Andersen et al 1 Das et al 8 Chen et al 5 Da ´vila et al 9 Edwards et al 11 Chun and Kim 7 Fazal et al 15 Fann et al 14 Dedeog˘lu et al 10 Flinkkila ¨et al 16 Flinkkila ¨et al 17 Erdle et al 12 Haidar et al 19 Fan et al 13 Hohmann et al 20 Hsu et al 21 Kanchanatawan and Wongthongsalee 23 Kraus et al 27 Kapil-Mani et al 24 Kuner et al 28 Kashii et al 25 Kwak et al 29 Klein et al 26 Lanier et al 30 Lee et al 31 Lee et al 32 Meda et al 41 Lee et al 33 Mirbolook et al 42 Lee et al 34 Nordqvist et al 46 Leu et al 35 Ranalletta et al 49 Li et al 37 Renger et al 50 Lopiz et al 39 Rokito et al 53 Loriaut et al 40 S xerban 55 Mochizuki et al 43 Seyhan et al 56 Ochen et al 47 Teoh et al 58 Robinson et al 51 Tiren et al 59 Seo et al 54 Varyani…”
Section: Good Qualitymentioning
confidence: 99%
“…In regard to combat experiences, we found that combat injuries and stressful combat events were common (20.2% and 46.4%, respectively) and associated with new postdeployment pain. That combat experiences were determinants of new pain has been previously shown and is intuitive (physical injury and acute pain can transition into chronic pain), while PTSD and other psychiatric comorbidities are common correlates of pain . Herein, combat experiences were used as a surrogate for PTSD and other psychiatric comorbidities because these traumatic experiences typically precede the manifestation of psychiatric sequelae .…”
Section: Discussionmentioning
confidence: 97%